Early Adulthood Perspective of a Well-Lived Life: A Basis for Self-Help Plan - De Leon, Camille; Nepomuceno, Ma. Rosario; Torres, Manuel (International Journal of Applied Guidance and Counseling, 2025)
The concept of a well-lived life among individuals in early adulthood mainly focus on how they navigate life transitions and achieve personal success. Utilizing a phenomenological approach, semi-structured interview was used with twelve Filipino young adults aged 25 to 35 years old. Thematic analysis revealed four major themes: Empowered Purpose, highlighting resilience and coping strategies; Building Bonds, emphasizing the importance of relationships and support; Art of Balance, addressing work-life harmony; and Behind the Persona, which explores the challenges and uncertainties faced by young adults. Findings suggest that a well-lived life is intricately tied to personal values, social connections, and the ability to adapt to life's complexities. The study contributes to understanding how young adults perceive fulfillment and success amid contemporary societal pressures, offering insights for practices in education, mental health, and social policy. The LIFE self-help plan is devised to help young adults engage in mindfulness and self-compassion practices in realizing a healthy concept of a well-lived life.